The Causality Relationship Between Growth and Inequality: Java and Sumatera Studies - Candra Mustika; Parmadi Parmadi; Emilia Emilia; Rahma Nurjanah (Economics Development Analysis Journal, 2023)
This research article has the theme of the causal relationship between growth and inequality with the object of research being the provinces on the island of Java and Sumatra island. The purpose of this study is to identify and analyze conditions of inequality in income distribution and economic growth and to analyze whether there is a causal relationship between inequality income with economic growth in provinces on the island of Java and provinces on the island of Sumatra during the 2015-2020 period. The research method used is quantitative descriptive using the Granger causality test analysis tool. Based on the research results, the condition of economic growth in each province on Sumatra Island fluctuated, with the highest average economic growth in South Sumatra Province and the lowest in Riau Province. Inequality in the distribution of provincial income on the island of Sumatra fluctuates, the highest average income distribution inequality is in the provinces of South Sumatra and Bengkulu, and the lowest is in the province of the Bangka Belitung Islands. Meanwhile in Java, economic growth also fluctuated. The highest average economic growth was in DI Yogyakarta Province, and the lowest was in Central Java Province. Inequality in the distribution of provincial income in Java Island fluctuates, with the highest inequality in Yogyakarta province and the lowest in Central Java province. In addition, the results of the Granger causality test show that there is no one-way or two-way causality relationship between economic growth and income inequality on the islands of Sumatra and Java.